Root growth of four transplant Aman rice varieties as influenced by NPKS fertilizer (Journal of the Bangladesh Agricultural University, 2010)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, during July to December 2006 to study the root growth of four Transplant Aman rice varieties as influenced by NPKS fertilization. The experiment was laid out in a split-plot design with three replications. The experiment consisted of four varieties viz. BRRI dhan30, BRRI dhan31, BRRI dhan40 and BRRI dhan41; and four levels of fertilizers viz. 0, 50%, 100% and 150% of the recommended dose of NPKS. BRRI dhan41 had better performance in all root parameters. All root parameters except number of roots hill-1 performed better at high level of fertilizer. The interaction effect between variety and fertilizer level was significant in respect of number of roots hill-1, fresh weight of root (except at 30 days after transplanting (DAT) and 90 DAT), dry weight of root, fresh weight of above ground plant part (except at 30 DAT and 90 DAT) and dry weight of above ground plant part (except at 90 DAT). Keywords: Root growth; Rice varieties; NPKS fertilizer DOI: 10.3329/jbau.v6i2.4816 J. Bangladesh Agril. Univ. 6(2): 235-238, 2008